2008
DOI: 10.1016/j.ssc.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency spectroscopy of superconducting photonic crystals

Abstract: Transmission, reflection and absorption of electromagnetic radiation and photon dispersion law for 2D photonic crystals with superconducting elements are studied. The calculation of optical properties of photonic crystals is studied by layer-by-layer Korringa-Kohn-Rostoker techniques. The results of numerical calculations performed for an array of superconducting cylinders have been understood in terms of a simple analytical model. The controlling of optical properties of superconducting photonic crystal by te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14] Another group of unconventional materials for PCs, namely, superconductors was also studied in a number of theoretical publications for 1D and 2D PCs. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] All the articles related to superconducting ͑SC͒ PCs were investigating regular ͑nondefect͒ structures. The interest to the SC PCs is due to their applications in a new type of resonators 34 and microstrip filters based on YBa 2 Cu 3 O 7 which work in the gigahertz regime.…”
Section: -3mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] Another group of unconventional materials for PCs, namely, superconductors was also studied in a number of theoretical publications for 1D and 2D PCs. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] All the articles related to superconducting ͑SC͒ PCs were investigating regular ͑nondefect͒ structures. The interest to the SC PCs is due to their applications in a new type of resonators 34 and microstrip filters based on YBa 2 Cu 3 O 7 which work in the gigahertz regime.…”
Section: -3mentioning
confidence: 99%
“…25 , 52 In the latter case, it was found that the gap is temperature dependent, due to the temperature dependence of the superfluid density, and therefore tunable. 52 , 53 , 54 , 62 , 57 High temperature cuprate superconducting materials have strongly anisotropic dielectric properties. They show metallic behavior for currents flowing in the Cu-O planes, and have dielectric-like properties for light polarized in the c-direction.…”
Section: Iii5mentioning
confidence: 99%
“…The high temperature superconductor YBCO is considered in the following calculations. Its parameters in normal state are x p ¼ 1.67 Â 10 15 rad/s, c p ¼ 1.34 Â 10 13 rad/s, and T c ¼ 91 K. 44 When the active system is pumped, the electromagnetic fields can be calculated using FDTD method to solve Eqs. (1), (2), and (7)- (10).…”
Section: -2mentioning
confidence: 99%